Tinjauan Yuridis Pemanfaatan Media Sosial sebagai sarana Promosi Online oleh Notaris sebagai Pelanggaran Kode Etik - Ramadhandiko, Difqa Alvi; Lewoleba, Kayus Kayowuan (Media Hukum Indonesia (MHI), 2025)
The phenomenon of the rapid development of social media has an impact on the notary profession as a public official. Notaries often use digital platforms such as Instagram to include their names and positions, which is categorized as covert promotion. In fact, based on the Notary Position Law and the Notary Code of Ethics, acts of self-promotion are prohibited because they can degrade the dignity of the profession. This research uses normative juridical method and case approach to examine the prohibition of promotion and the sanctions that can be imposed. The results show that supervision of ethical violations in the digital space has not been optimal, and existing sanctions have not provided a deterrent effect. Therefore, it is necessary to strengthen the supervision system and enforcement of sanctions to maintain the integrity of notaries. This research is expected to contribute to the renewal of notary professional ethics in the digital era.